Drained Inland Organic Soils - Drösler, M.; Verchot, Louis V.; Pan G; Freibauer, A.; Evans, C.D.; Bourbonniere RA; Alm JP; Page S; Agus, F.; Sabiham S; Wang C; Srivastava N; et al. (Intergovernmental Panel on Climate Change, 2013)
Organic soils are defined in Chapter 3 Annex 3A.5 of Volume 4 of the 2006 IPCC Guidelines and Section 5, Chapter 1, section 5 of this Wetlands Supplement. The guidance in this Chapter applies to all inland organic soils that have been drained, i.e., drainage of lands that started in the past and that still persists, or newly drained lands within the reporting period. This means that the water table level is at least temporarily below natural levels. Natural levels mean that the mean annual water table is near the soil surface but can experience seasonal fluctuations. Within each land-use category water table level is manipulated to varying degrees depending on land-use purpose, e.g., for cultivating cereals, rice, or for aquaculture, which can be reflected by different drainage classes. This Chapter deals with inland organic soils, which do not meet the definition of “coastal” defined in Chapter 4 of this Wetlands Supplement.The term “organic soils” refers to “inland organic soils” in this Chapter. This Chapter provides supplementary guidance on estimating greenhouse gas emissions and removals from drained inland organic soils in the following land-use categories as defined in the 2006 IPCC Guidelines Volume 4: Chapter 4 (Forest Land), Chapter 5 (Cropland), Chapter 6 (Grassland), Chapter 7 (Wetlands), Chapter 8 (Settlements) and Chapter 9 (Other Land). Managed coastal organic soils are covered in Chapter 4 of this Supplement. Rewetted organic soils are considered in Chapter 3 of the Wetlands Supplement.